Gerontogimnasia para mejorar la coordinación y equilibrio en usuarios del centro de atención integral al adulto mayor-Guano, 2017-2018 - Saca Núñez, Elida Aracely (2018)
The research project was carried out through a transversal, field, documentary, applicative, inductive - deductive and qualitative and quantitative study. The population was with 25 eldery people at age of 60 years. The objective was to apply the gerontogimnasia in the patients with risk of falling, to improve coordination and balance in users of the Integral Attention Center for the Elderly-Guano. Only users of the institution with a deficit in coordination and balance and a tendency to suffer falls were included, and patients with a high degree of dependency were excluded, as well as those older adults who presented with disability or serious illnesses and who did not want to be part of the program. investigation project. The analysis of results was obtained by means of the statistical analysis of the data obtained in the clinical records, physiotherapy and the Tinetti test, Modified Romberg and coordination, by means of an initial and final physiotherapeutic evaluation. The study showed that there is a predominance of females and a greater population of users from 71 to 75 years of age. The protocol of exercises for coordination and balance was elaborated, which consisted of three circuits: Circuit 1 - Warm up exercises; Circuit 2 - Coordination and balance exercises in two levels according to the progression of the patient and circuit 3 - Return to calm. With this protocol of exercises executed in an orderly, planned way that demonstrates that it is an effective tool for the improvement of the evolution and balance and that they have a high effectiveness at the moment of the verification of the evolution of the patient.